2010
DOI: 10.1182/blood-2009-11-255497
|View full text |Cite
|
Sign up to set email alerts
|

Extreme lymphoproliferative disease and fatal autoimmune thrombocytopenia in FasL and TRAIL double-deficient mice

Abstract: To delineate the relative roles of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and Fas ligand in lymphocyte biology and lymphoproliferative disease, we generated mice defective in both molecules. B6.GT mice develop severe polyclonal lymphoproliferative disease because of accumulating CD3 ؉ CD4 ؊ CD8 ؊ B220 ؉ T cells, CD4 ؉ and CD8 ؉ T cells, and follicular B cells, and mice die prematurely from extreme lymphocytosis, thrombocytopenia, and hemorrhage. IntroductionApoptotic cell death is med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 52 publications
1
25
1
Order By: Relevance
“…In a word, the total TRAIL expression on the platelet surface of group A might be in a much lower level, which may enhance the role of TRAIL in impaired megakaryocyte apoptosis through the TRAIL/ TRAIL-R2 pathway. Recently, Sedger et al 44 have reported that FasL and TRAIL double deficient mice develop extreme lymphoproliferative disease and fatal autoimmune thrombocytopenia, which is a little different from the results of our study. However, severe lymphoproliferative disease is the result of maximal resistance of lymphocytes to activation-induced cell death, and dysregulated lymphocyte homeostasis resulted in the production of antiplatelet IgM and IgG causing thrombocytopenia.…”
Section: Trail-mediated Megakaryocyte Apoptosis 4313contrasting
confidence: 99%
“…In a word, the total TRAIL expression on the platelet surface of group A might be in a much lower level, which may enhance the role of TRAIL in impaired megakaryocyte apoptosis through the TRAIL/ TRAIL-R2 pathway. Recently, Sedger et al 44 have reported that FasL and TRAIL double deficient mice develop extreme lymphoproliferative disease and fatal autoimmune thrombocytopenia, which is a little different from the results of our study. However, severe lymphoproliferative disease is the result of maximal resistance of lymphocytes to activation-induced cell death, and dysregulated lymphocyte homeostasis resulted in the production of antiplatelet IgM and IgG causing thrombocytopenia.…”
Section: Trail-mediated Megakaryocyte Apoptosis 4313contrasting
confidence: 99%
“…TRAIL-deficient mice have been reported to have defects in the thymic negative selection and control of central tolerance, with consequences for the development of autoimmune diseases [37, 38] although not confirmed in other studies [39]. Sedger et al reported that control of aberrant lymphocyte expansion requires both FasL and TRAIL and only the double KO mice show a marked lymphoproliferative disease and severe autoimmunity [40]. Thus TRAIL in tandem with FasL are important to control lymphocyte homeostasis and to limit autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…The TRAIL-R/TRAIL system was previously described to contribute to T cell homeostasis because blocking Abs against TRAIL reduced the efficiency of activation-induced cell death (31), and mice deficient for CD95L and TRAIL developed a more severe lymphoproliferative disease than mice deficient for CD95L alone (32). Also, "helpless" CD8 + Ag-activated T cells generated in the absence of CD4 + T cells die by TRAIL-mediated, activationinduced cell death upon restimulation (33).…”
Section: Discussionmentioning
confidence: 99%